Trade and Development Report 1989 - Conference des Nations Unies sur le commerce et le développement (United Nations, 1989)
Global output and trade expanded very rapidly last year and are continuing to grow, though at a somewhat reduced pace. The international economy is apparently in good health. However, this appearance is misleading. The growth impulses that are present are quite fragile, and will need to be actively protected.